Addressing Rural Issues in Urban Planning: Emerging Trends and Reflective Perspectives - Kuldeep Kumar; Luvditya Khurana; Devendra Pratap Singh (International Journal of Rural and Regional Development, 2024)
Urban planning, a crucial component in shaping the future of communities, has traditionally been entered on urban spaces, often neglecting the unique challenges faced by rural areas. This paper delves into the critical intersection of rural issues within urban planning, analysing current trends and providing reflective perspectives on integrating rural considerations. By examining emerging trends such as rural-urban linkages, sustainable agriculture, rural infrastructure development, and technology adoption, this paper explores how urban planners can contribute to holistic and sustainable development. Challenges such as limited resources, policy alignment, and community engagement are discussed, emphasizing the need for adaptive strategies. The paper focuses on reflective perspectives on lessons learned and successful strategies along with the insights gained from case studies, particularly within the Indian context. The findings highlight the importance of recognizing and addressing rural issues for a more inclusive and resilient urban future, providing recommendations for future urban planning endeavours.
Keywords: Rural Infrastructure; Rural populations; sustainable; urban environments; urban planning